Maternal Chronic Periodontitis as a Risk Factor for Preterm Birth and Low Birth Weight: A Hospital-Based Case Control Study (Academia Journal of Medicine, 2025)
Background: Preterm birth (PTB) and low birth weight (LBW) are main causes of neonatal morbidity and mortality worldwide. Evidence suggests a potential link between maternal chronic periodontitis and adverse pregnancy outcomes. Objectives: This hospital-based case-control study aimed to assess the association between maternal chronic periodontitis and the risk of preterm birth and low birth weight in postpartum women. Methods: A total of 540 postpartum women were enrolled, comprising 270 cases (PTB and/or LBW) and 270 matched controls (term and normal birth weight). Demographic data and obstetric history were recorded. Periodontal status was assessed using the Clinical Attachment Loss (CAL) index, Gingival Index, and Community Periodontal Index of Treatment Needs (CPITN). Results: No significant differences were observed between groups regarding age, gravidity, or educational status (p > 0.05). However, periodontal indicators were significantly worse among cases. The mean CAL score was higher in the case group (4.18 ± 1.05) than controls (3.8 ± 0.83; p = 0.002). Gingival inflammation and CPITN scores also showed significant differences (p < 0.001) Conclusion: Maternal chronic periodontitis is significantly associated with preterm birth and low birth weight. Early diagnosis and management of periodontal disease in pregnant women may play a role in improving perinatal outcomes.
Keywords: Periodontitis; Preterm birth; Low birth weight; Pregnancy; Case-control study; CPITN